VARIABEL YANG BERPENGARUH TERHADAP PRODUKTIVITAS ANGKUTAN BATUBARA YANG MELALUI KOTA BANJARMASIN - Bachtiar, Yunik; N. Pratama, Muhammad; Jinca, M. Yamin (Jurnal Transportasi, 2010)
Many factors influence drivers to select the best route for their travel. With this reason, truck drivers carrying coal in Banjarmasin area have to find what routes give them the most benefit to transport coal from coal mines to stockpiles. This study aims to determine factors affecting the productivity of trucks transporting coal through road network in the city of Banjarmasin. The results show that only travel time and vehicle types affect the truck productivity significantly.Keywords: truck productivity, road network, and coal transport.